2015
DOI: 10.1021/ef502874p
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Kinetics Study on the Heating Stage of the Shenhua Direct Coal Liquefaction Process

Abstract: Direct coal liquefaction in the heating stage of Shenhua Shendong bituminous coal was carried out in a 0.01 t/d continuous tubular facility with iron catalyst and hydrogenated anthracene and wash oil as solvent at a residence time (t) of 3.5− 6.5 min and a reaction temperature (T) of 340−450 °C. The results show that when t = 3.5 min and T = 340 °C, a cracking reaction of coal occurs, while the oil yield was almost zero. As the residence time and temperature each increase, coal conversion and product yield exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…This may be attributed to the thermal decomposition of some substances in the compounds. The percentage of compounds represented by peak 1 of NS showed a maximum value, and its M w also increased during this interval, which indicates the migration of components of BS and TS to NS and the further decomposition of some of the thermosensitive substances present therein.…”
Section: Resultsmentioning
confidence: 84%
“…This may be attributed to the thermal decomposition of some substances in the compounds. The percentage of compounds represented by peak 1 of NS showed a maximum value, and its M w also increased during this interval, which indicates the migration of components of BS and TS to NS and the further decomposition of some of the thermosensitive substances present therein.…”
Section: Resultsmentioning
confidence: 84%
“…Cugini [25] reported that liquefaction feed coal not only promoted the generation of ultrafine FeOOH but also assisted in dispersing the Fe1−xS that was generated in situ during DCL. It is worth noting that ultrafine γ-FeOOH catalysts supported on coal have been successfully applied in the first megaton DCL industrial demonstration plant, operated by the Shenhua Group [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…A coal‐to‐liquids company in China has the first direct coal liquefaction production line for commercial operation in the world, which was put into operation at 2009 . As the commencement, the corrosion on the internal bottom plate of various tanks for liquid hydrocarbon storage occurred frequently, which has resulted in the leakage of flammable materials .…”
Section: Introductionmentioning
confidence: 99%